2020
DOI: 10.14233/ajchem.2020.22591
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Sterols from Philippine Mushrooms

Abstract: Ergosterol peroxide (1) and ergosterol (2) were commonly isolated as the major compounds of Philippine mushrooms. Sterols 1 and 2 from the dichloromethane extract of Geastrum triplex and Termitomyces clypeatus, respectively, were evaluated for their cytotoxic activities against four human cancer cell lines, viz., breast cancer (MCF-7), colon cancer (HT-29), leukemia (THP-1), and small lung cell carcinoma (H69PR), and a human normal cell line, human dermal fibroblast-neonatal (HDFn), using the PrestoBlue® cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…On the other hand, the presence of ergosterol has been found in P. florida, P. djamor, and P. eryngii (Ragasa, 2018). Ergosterol is a precursor of vitamin D2 produced via exposure to UV light, and exhibits antioxidant activity and prevents cardiovascular diseases (Selvamani et al, 2018;González et al, 2021;Koutrotsios et al, 2022).…”
Section: Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the presence of ergosterol has been found in P. florida, P. djamor, and P. eryngii (Ragasa, 2018). Ergosterol is a precursor of vitamin D2 produced via exposure to UV light, and exhibits antioxidant activity and prevents cardiovascular diseases (Selvamani et al, 2018;González et al, 2021;Koutrotsios et al, 2022).…”
Section: Lipidsmentioning
confidence: 99%
“…It has been observed that crude extracts and chemical fractions from Pleurotus fruiting bodies or mycelium contain compounds that exhibit anticancer effect toward several types of tumour cells, but this activity depends on the species. Extracts from P. pulmonarius, P. florida, and P. djamor have demonstrated efficacy against several cancer types or cell lines, including human hepatoma HepG2 cells, bladder carcinoma, and ovarian cancer, respectively (Selvi et al, 2011;Xu et al, 2012;Ragasa, 2018).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Mushrooms, including L. tigrinus, C. comatus, P. cyanescens, P. antillarium, L. sajor-caju, L. strigosus, P. grammocephalus, T. elegans, Trichaleurina celebica, P. cystidiosus, P. sanguineus, and Xylaria papulis, have been shown to contain carbohydrates, proteins, crude fibers, crude fat, vitamins, and minerals and important bioactive metabolites such as alkaloids, flavonoids, phenols, coumarins, triterpenes, tannins, saponins, anthraquinones, athrones, and steroids [48,65,118,126,135,140,141,[146][147][148][149][150][151][152][153]. Other mushrooms, namely, C. reinakeana, C. comatus, V. volvacea, G. lucidum, P. cystidiosus, L. tigrinus, L. sajor-caju, Geastrum triplex, T. clypeatus, and S. commune have also been reported as source of amino acids, fatty acids, acyglycerols, triacylglycerols, ergosterol, and minerals [111,127,[154][155][156][157][158][159][160][161].…”
Section: Nutritional and Medicinal Properties Of Philippine Mushroomsmentioning
confidence: 99%
“…The therapeutic values and medicinal properties of edible mushrooms have found to stem from numerous biologically active compounds or metabolites [162][163][164]. Besides nutrients and active metabolites, Philippine mushrooms have been revealed to exhibit important bioactivities, including antioxidants [48,126,128,[133][134][135]147,[150][151][152][153]165,167] antibacterial [59,118,135,146,150,152,[167][168][169]] hypoglycemic [146,170] antihypertensive [154,155,171] anticancer [160,[172][173][174] anticoagulative, anti-inflammatory [154][155][156]175] teratogenic [65,148,[176][177][178][179][180][181]…”
Section: Nutritional and Medicinal Properties Of Philippine Mushroomsmentioning
confidence: 99%
“…Studies on the cytotoxic and/or anticancer activities of Philippine endemic and indigenous mushrooms are limited. Ergosterol peroxide and ergosterol from dichloromethane extracts of Geastrum triplex and Termitomyces clypeatus , respectively, exhibited cytotoxic activities against breast cancer (MCF-7), colon cancer (HT-29), and small lung cell carcinoma (H69PR) [ 12 ]. A water-insoluble polysaccharide extract from Lenzites betulina showed strong cytotoxic effects against K562 leukemia cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%